2018
DOI: 10.1007/s10653-018-0163-3
|View full text |Cite
|
Sign up to set email alerts
|

Urban geochemistry and potential human health risks in the Metropolitan Area of Buenos Aires: PAHs and PCBs in soil, street dust, and bulk deposition

Abstract: Soil, street dust, and bulk deposition (dry and wet deposition) were collected in the Metropolitan Area of Buenos Aires (MABA), Argentina, to assess the polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) pollution and the potential risks to human health. Compared with other countries, the mean concentration of PAHs and PCBs in surface soils, street dust and bulk deposition of MABA were at a low or moderate level. Average PAHs and PCBs concentrations in bulk deposition (5.7 ± 5.1 and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…At the same time, street dust particles are a source of pollutants in roadside soils (Prokof'eva et al 2017;Ró _ zański et al 2017;Pariente et al 2019), which can re-enter the atmosphere through resuspension (Jordanova et al 2014) or migrate with surface runoff and stormwater (Calvillo et al 2015;Liu et al 2016). Numerous studies are devoted to the status of various pollutants, primarily PTEs and PAHs, in street dust in some of the world's largest megacities, industrial production centres (Liu et al 2007;Saeedi et al 2012;Acosta et al 2014;Yu et al 2014;Soltani et al 2015;Bandowe and Nkansah 2016;Tang et al 2017;Men et al 2018;Cappelletti et al 2019), cities, and towns (Majumdar et al 2017;Ghanavati et al 2019;Zhaoyong et al 2019). The results of these studies have shown that accumulation of pollutants in street dust and near road environments is influenced by a wide range of factors, including population density, traffic, degree of soil sealing, age and type of automobiles, climate, and geological conditions of a particular territory (Charlesworth et al 2003;Shi et al 2010;Wei et al 2010;Zhang et al 2015;De Silva et al 2016;Trujillo-González et al 2016;Yan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, street dust particles are a source of pollutants in roadside soils (Prokof'eva et al 2017;Ró _ zański et al 2017;Pariente et al 2019), which can re-enter the atmosphere through resuspension (Jordanova et al 2014) or migrate with surface runoff and stormwater (Calvillo et al 2015;Liu et al 2016). Numerous studies are devoted to the status of various pollutants, primarily PTEs and PAHs, in street dust in some of the world's largest megacities, industrial production centres (Liu et al 2007;Saeedi et al 2012;Acosta et al 2014;Yu et al 2014;Soltani et al 2015;Bandowe and Nkansah 2016;Tang et al 2017;Men et al 2018;Cappelletti et al 2019), cities, and towns (Majumdar et al 2017;Ghanavati et al 2019;Zhaoyong et al 2019). The results of these studies have shown that accumulation of pollutants in street dust and near road environments is influenced by a wide range of factors, including population density, traffic, degree of soil sealing, age and type of automobiles, climate, and geological conditions of a particular territory (Charlesworth et al 2003;Shi et al 2010;Wei et al 2010;Zhang et al 2015;De Silva et al 2016;Trujillo-González et al 2016;Yan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The total CR and HQ risks for adults and toddler were 3.16 × 10 −05 and 4.32 × 10 −04 , and 7.90 × 10 −07 and 1.08 × 10 −05 , respectively. When these results were compared with the lifetime cancer risk threshold established by the Agency for Toxic Substances and Disease Registry (ATSDR) (very low (≤10 −6 ) to very high (≥10 −1 )), it was found that the adults were prone from low to moderate cancer risk as compared to toddlers, which were susceptible to the relatively high lifetime cancer risk 40,67 . For the non‐carcinogenic risk, the measured values of total HQ were found to be lower than the tolerable limit of ≤1 8 .…”
Section: Resultsmentioning
confidence: 92%
“…For the non‐carcinogenic risk, the measured values of total HQ were found to be lower than the tolerable limit of ≤1 8 . Overall, the toddlers were potentially more exposed to PCB contamination and were at high risk as compared to the adults because of their lower body weight, less developed immune system, frequent hand to mouth activities and crawling 67 …”
Section: Resultsmentioning
confidence: 93%
“…These particles behave similar to atmospheric aerosols and may be re-suspended onto or re-deposited from the atmosphere [1]. As street dust consists of large proportion of fine particles, organic or inorganic contaminants in street dust can easily enter the human body particularly via inhalation, ingestion or direct absorption by skin [2,3]. Exposure to street dust of respirable size itself presents a health risk and can lead to a range of lung diseases.…”
Section: Introductionmentioning
confidence: 99%